A proposal to delegate GUI implementation using a source code based model - Monteiro, Marco (2009)
In this paper we propose an architecture whose main goal is to improve productivity in user interface development for data-intensive applications. This objective is to be achieved by defining a high level model that describes the user interface structure. That model will be integrated in the source code through non-functional language extensions. Our final goal is allowing developers to define user interface model by adding language extensions to the source code and then acquiring an external software package to which they delegate the implementation of the concrete user interface.